Gearing up for '95 and beyond ; And justice for all ; Viva Mexico [videorecording] - Lazaro, Cheche (The Probe team, 1994)
The first part is about the formation of LAKAS-NUCD-LDP coalition; The second part is about Dr. Juliet Dumlao sentenced to twenty years in prison for a federal crime in the United States; The third part shows the artistic performance of Mexicans who visited the Philippines in the celebration of their 184th year of independence.